Synthesis and computational simulation of new phosphorilated sulfoximines with insecticidal activity - Bellozas Reinhard, M.E. (2000)
New organophosphorus insecticides of dialkylsulphoximines derived with activity upon acetylcholinesterase were synthesized. The obtained compounds were characterized by NMR and IR, and anticholinesterase activity and toxicity was measured. A simulation through computer was done in order to establish the relationship between structure and activity.